2022
DOI: 10.1021/acsami.1c23962
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Linked PVA/HNT Composite Separator Enables Stable Lithium-Organic Batteries under Elevated Temperature

Abstract: Li-organic batteries (LOBs) are promising advanced battery systems because of their unique advantages in capacity, cost, and sustainability. However, the shuttling effect of soluble organic redox intermediates and the intrinsic dissolution of smallmolecular electrodes have hindered the practical application of these cells, especially under high operating temperatures. Herein, a cross-linked membrane with abundant negative charge for hightemperature LOBs is prepared via electrospinning of poly(vinyl alcohol) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…AC/ANT does not show a redox peak in its voltammogram, while a distinct reversible peak couple is observed for AC/ANT-Ox between −0.2 and 0.05 V. It has been reported that AQ-adsorbed porous carbons show reversible redox peaks in the same potential range when using the same electrolyte, 21 whereas the redox potential depends on the kind of electrolytes. 22 Given the reversible redox peak potential of AC/ANT-Ox, ANT was expected to be transferred to AQ by electrochemical oxidation. Indeed, the shape of the voltammogram of AC/ANT-Ox is similar to that of AC/AQ, suggesting that the ANT in AC/ANT was electrochemically oxidized to AQ.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AC/ANT does not show a redox peak in its voltammogram, while a distinct reversible peak couple is observed for AC/ANT-Ox between −0.2 and 0.05 V. It has been reported that AQ-adsorbed porous carbons show reversible redox peaks in the same potential range when using the same electrolyte, 21 whereas the redox potential depends on the kind of electrolytes. 22 Given the reversible redox peak potential of AC/ANT-Ox, ANT was expected to be transferred to AQ by electrochemical oxidation. Indeed, the shape of the voltammogram of AC/ANT-Ox is similar to that of AC/AQ, suggesting that the ANT in AC/ANT was electrochemically oxidized to AQ.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Therefore, the amounts of AC per 1 cm 3 of the electrodes can be regarded as the same for all the samples, and the current per 1 g of AC is correlated with the current per unit electrode volume (i.e., the volumetric current). AC/ANT does not show a redox peak in its voltammogram, while a distinct reversible peak couple is observed for AC/ANT-Ox between −0.2 and 0.05 V. It has been reported that AQ-adsorbed porous carbons show reversible redox peaks in the same potential range when using the same electrolyte, whereas the redox potential depends on the kind of electrolytes . Given the reversible redox peak potential of AC/ANT-Ox, ANT was expected to be transferred to AQ by electrochemical oxidation.…”
Section: Resultsmentioning
confidence: 99%
“…S10, ESI†). 17,24 Overall, the electrochemical performance indicated that the PSE11-Gel separator is a good solution for fabricating high-performance and stable LOBs.…”
mentioning
confidence: 93%
“…For example, Fartash et al [26] prepared PAN/PVA/MA separators via electrospinning, using malonic acid (MA) as a crosslinking agent with enhanced tensile strength and reduced thermal shrinkage. In another research, Gong et al [27] fabricated the PVA/HNT composite separator via the electrospinning of PVA containing halloysite nanotubes (HNTs), followed by crosslinking via immersion in a glutaraldehyde dispersion. The PVA/HNT separator showed excellent thermal stability and mechanical properties due to the interlocking interconnections between the thermally resistant HNTs and the PVA matrix.…”
Section: Introductionmentioning
confidence: 99%